SURVEI MINAT SISWA-SISWI DALAM PEMBELAJARAN PENJAS DI SMP NEGERI 3 SAMALANTAN - Novita, Risna; Supriatna, Eka; Puspitawati, Isti Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
ABSTRACT: The research problem is how the students' interest in learning physical education at the First Middle School State 3 Samalantan.Research purposes to determine students' interest in learning physical education at the First Middle School State 3 Samalantan. The study population was all students in Middle School First School 3 Samalantan the following physical education teaching 162 students, sampling using random sampling techniques to obtain samples 77. Form of quantitative descriptive research using survey techniques. Research variable interest students in learning physical education. Research instrument using a questionnaire. Results of testing 20 question questionnaire is valid, reliability figure 0.973. Research shows students' interest in learning physical education in Middle School First School 3 Samalantan: 1) The success of self-42.78%; 2) Accept the learning of physical education with fun 47.73%; 3) The desire to do something 46.49%; 4) always present in the following study physical education 48.05%; 5) Improving physical fitness of 53.25%; 6) Methods of teaching physical education play in the 42.21%; 7) Facility 42.21%; 8) Curiosity 38, 10%. Conclusions: Interest in learning physical education students in Middle School First School 3 Samalantan done well, averaging 40.31% very good category. Keywords: Interest in teaching physical education ABSTRAK:Permasalahan penelitian adalah bagaimanakah minat siswa dalam pembelajaran penjas di SMPN 3 Samalantan. Tujuan penelitian untuk mengetahui minat siswa dalam pembelajaran penjas di SMPN 3 Samalantan. Populasi penelitian adalah seluruh siswa SMPN 3 Samalantan yang mengikuti pembelajaran penjas 162 siswa, pengambilan sampel menggunakan teknik sampel random sampling sehingga diperoleh sampel 77. Bentuk penelitian Deskriptif Kuantitatif menggunakan teknik survei. Variabel penelitian minat siswa dalam Pembelajaran Penjas. Instrumen penelitian menggunakan angket. Hasil uji coba angket 20 soal dinyatakan valit angka reabilitasnya 0,973 Penelitian menunjukan minat siswa dalam pembelajaran penjas di SMPN 3 Samalantan: 1) keberhasilan diri 42,78%; 2) menerima pembelajaran penjas dengan senang 47,73%; 3) keinginan mengerjakan sesuatu 46,49%; 4) selalu hadir dalam mengikuti pembelajaran penjas 48,05%; 5) meningkatkan kebugaran jasmani 53,25%; 6) metode bermain dalam pembelajaran penjas 42,21%; 7) fasilitas 42,21%; dan rasa ingin tahu 38,10%. kesimpulan: Minat siswa dalam pembelajaran penjas di SMPN 3 Samalantan terlaksana dengan baik, rata-rata 40,31% kategori sangat baik. Kata kunci: Minat Pembelajaran Penjas